Role of bioengineering and laborers in integration of farmland resources toward to improve dimension of sustainable agriculture in China. Issue 1 (1st January 2020) - Yu, Xinyou; Liu, Yunqing; Wang, Yiwen; Feng, Xiaoli; Tu, Mingzhong; Chen, Jiangsheng
ABSTRACT: Farmland transfer is one of the essential approaches for achieving large-scale farming and its management affects productive efficiency, environment pollution and food sustainable security supply. Present study was carried out investigation based representative agricultural development area Guanzhong Plain of Shaanxi, aimed at explore the role of biotechnology and laborers in integration of farmland toward to improve sustainable agriculture in rural China by employed the profit and Tobit models evaluation. The conclusion demonstrated that labor's and agricultural management model as main stay, intensive farming has positive effect-based economic and environmental benefits than fragmentation management, female laborers have weaker effect on farmland renting-out behavior among smallholders while male laborers were superior promoters in increasing the area of rented-in farmland and farm scale. Finally, bioengineering development and agricultural intensification management as a rational choice that has great potential value for large-scale cultivation that contributing a promising future for achieving cleaner production, environment and human health further providing huge economic and social and environmental benefits in sustainability agriculture. Additionally, government policies require intensive intervention to accelerate large-scale management and biotechnology implementation. Abbreviation : Aaflf : Average age of female labor force; In com (log) : Log of annual household income; Noflf : Number of women in the labor force; Nooaf : Number of old adults in family; NTFs: non-transfer families; OLS: ordinary least square; Palff : Proportion of agricultural laborers in the female labor force; Palmf : Proportion of agricultural laborers in the male labor force; RIFs: rented-in families; ROFs: rented-out families; Whhf : Whether the household head is female Graphical abstract: